FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU KONSUMEN DALAM MENGKONSUMSI BUAH JERUK IMPOR DI KOTA PALU - Nur Jannah; Made Antara; Effendy Effendy (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
This study aim was to determine factors influencing consumer behavior in consuming imported citrus in Palu city and it was conducted from May to June 2017.  Data was analyzed using a logistic regression analysis. The results of the research showed that the factors influencing the consumer to consume the imported fruit were taste, income, number of dependents, and level of education to consumer behavior. Of the factor, the taste, the income and the education level were significantly affected the consumer behavior whereas the dependent numbers had no significant effect.